Community Socioeconomic Deprivation Predicts Nonalcoholic Steatohepatitis. Issue 3 (20th October 2021) - Giammarino, Alexa M.; Qiu, He; Bulsara, Kishen; Khan, Sabrina; Jiang, Yu; Da, Ben L.; Bernstein, David E.; Satapathy, Sanjaya K.
Abstract : In order to determine the relationship between socioeconomic deprivation and nonalcoholic fatty liver disease (NAFLD)/nonalcoholic steatohepatitis (NASH), we retrospectively reviewed the electronic medical records of 1, 430 patients in a large tertiary health care network in New York. These patients underwent liver biopsy over a 10‐year period and were included in our study if they had evidence of NAFLD/NASH on liver biopsy. Zip codes were used to obtain data necessary to derive the social deprivation index (SDI) from the US Bureau of the Census. The high‐SDI group was compared to the low‐SDI group. Univariate and multivariate logistic regressions were performed to assess association between socioeconomic factors and NAFLD parameters, including presence of NASH (NAFLD activity score >4), moderate to severe steatosis (>33%), and significant fibrosis (S2‐S4). We included 614 patients with NAFLD/NASH; the median SDI was 31.5. Hemoglobin A1c values were higher in the high‐SDI group compared to the low‐SDI group (6.46 vs. 6.12, P = 0.02). Socioeconomic factors, such as private versus public health care, percentage being foreign born, percentage without a car, percentage with higher needs (<5 years old and >65 years old), and percentage currently living in renter‐occupied and crowded housing units, showed statistically significant associations in predicting NASH. After adjusting for patient age, sex, race, body mass index, and diabetes, we saw a significant association between four or more socioeconomic parameters in predicting NASH (odds ratio [OR], 1.71; 95% confidence interval [CI], 1.099‐2.856; P = 0.0190) and six or more socioeconomic parameters in predicting severe steatosis (OR, 1.498; 95% CI, 1.031‐2.176; P = 0.0338) but no significant correlation between the number of socioeconomic parameters and significant fibrosis. Conclusion: Greater number of socioeconomic determinants (four or more) are associated with greater severity of NASH. Awareness of NAFLD/NASH needs to be raised in communities with high socioeconomic deprivation. Abstract : image